The Development of Physics Learning Tools with Problem-Based Learning Models to Improve Students' Critical Thinking Skills - Husna, Salsabila; Susanto, Duwi; Perdana, Riki (Department of Physics Education, Universitas Mataram, 2024)
The problems that are still encountered in physics learning are related to the role of the teacher who still dominates during the learning, causing students to become less active and students' critical thinking skills to become low. This study aims to determine the feasibility of physics learning tools developed using a problem-based learning model designed to improve students' critical thinking on harmonious vibration material. The research method used is Research and Development (R&D) with a 4D type of research. The instrument used is in the form of a validation sheet filled out by one expert lecturer and three Physics Education students. The results of the validation sheet are analyzed using the Likert scale technique and then categorized in the cumulative score range of product eligibility. The results of the research obtained through aspect tests on the learning tools show that the physics learning tools developed using problem-based learning models on harmonious vibration materials is very feasible to be used as an alternative to learning with presentations that can improve students' critical thinking skills. For further research, the products developed can be put through the next stage of development, namely the limited trial stage to find out their validity and empirical reliability. Then, they can be put through the effectiveness trial stage to find out whether they can be used in in schools.